Fractional Kinetic Models for Drying Using a Semi-Empirical Method in the Framework of Different Types of Kernels - Ercan, Ahu (Mdpi, 2025)
In this study, we analyze the Lewis model within the framework of the Caputo-Fabrizio fractional derivative in the sense of Caputo (CFC), the Caputo-type Atangana-Baleanu (ABC) fractional derivative and the generalized ABC with a three-parameter Mittag-Leffler kernel using a semi-empirical method. We derive some novel analytic solutions for fractional kinetic models with the help of Laplace transforms. We also provide comparative visual representations of the solutions through graphs, using kinetic data for soybean drying at temperatures of 50, 60, 70 and 80 degrees C. The comparative solutions derived from kinetic data reveal the fundamental symmetrical behavior of the drying process at different temperatures.
Keywords: fractional kinetic models; Atangana-Baleanu fractional derivative; Caputo-Fabrizio fractional derivatives; generalized ABC derivative; comparative analysis